Experimental study of 2-layer regenerators using Mn–Fe–Si–P materials. (16th February 2018) - Christiaanse, T V; Trevizoli, P V; Misra, Sumohan; Carroll, Colman; van Asten, David; Zhang, Lian; Teyber, R; Govindappa, P; Niknia, I; Rowe, A
Abstract: This work describes an experimental study of a two layer active magnetic regenerator with varying transition temperature spacing. The transition temperature of the materials is based on the specific heat peak of the materials. A transition temperature based on the average of the heating and cooling curves at zero Tesla field value is used to refer to the materials throughout this paper. This study uses five Mn–Fe–Si–P materials with transition temperatures of 294.6 K, 292.3 K, 290.7 K, 282.5 K and 281.4 K. Six different regenerators are tested. A reference configuration is tested using the 294.6 K material a hot side layer and with a second passive layer of lead spheres as cold side layer. Followed by four configurations that use the same 294.6 K material as hot side layer, but where each configuration uses a different cold side material. For the second active layer the materials are used in sequence; 292.3 K, 290.7 K, 282.5 K and 281.4K. Lastly, a sixth configuration uses the 292.3 K and 282.5 K materials. For each configuration, the temperature span is measured for rejection temperatures from 40 °C to 9 °C and at 0 W and 2 W applied load. Experimental results for temperature span and exergetic cooling power are compared based on the differences from the reference configuration. Materials are analysed based on material performance metrics such as peak adiabatic temperature change, peak entropy change and RCP(s) values. For the cases considered, a closer transition temperature spacing generally gives a greater temperature span and exergetic cooling power than further spaced materials, even when the combined materials have comparatively lower performance metrics. When two materials with higher RCP(s) values with large transition temperature spacing are compared to materials with lower RCP(s) values but, closer transition temperature spacing a higher exergetic cooling power and temperature span is found for the latter.